The Role of Students’ Quantitative Reasoning in Solving Mathematical Problems Based on Cognitive Style - Muhammad Muzaini; Muhammad Hasbi; Nasrun Nasrun (Universitas Islam Lamongan, 2021)
The emphasis of this research was how quantitative reasoning played an active role based on the cognitive style in addressing mathematical problem issues in middle school students. Participants in this study were students of a public middle-school, South Sulawesi, Indonesia. The findings revealed that Field-Independent students may define a problem or circumstance that solves the problem at hand, pick the relation between the quantities, and make quantity and relation-centered calculations. Second, Field-Dependent students use quantitative reasoning to consider the problem context, concentrate on the problem context quantity, deduce the relationship between quantities in the plans produced. The findings of this study are important for developing effective quantitative reasoning as input material for teachers